1993
DOI: 10.1172/jci116179
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony-stimulating factor is indispensable for both proliferation and differentiation of osteoclast progenitors.

Abstract: The mechanism of action of macrophage colony-stimulating factor (M-CSF) in osteoclast development was examined in a co-culture system of mouse osteoblastic cells and spleen cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
339
2
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(357 citation statements)
references
References 30 publications
9
339
2
4
Order By: Relevance
“…Clinical scores for the mice were determined for each of the four paws on study days [16][17][18][19][20][21][22][23][24][25][26][27][28]. The scores for all the four paws were given using the following criteria: 0, normal joints; 1, swelling in one digit or joint or minimal diffuse erythema; 2, swelling in two digits or joints or mild diffuse erythema; 3, swelling in three digits or joints or moderate diffuse erythema; 4, swelling in four digits or joints or marked diffuse erythema; 5, severe diffuse erythema and severe swelling of the entire paw and rigid joints.…”
Section: Collagen-induced Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical scores for the mice were determined for each of the four paws on study days [16][17][18][19][20][21][22][23][24][25][26][27][28]. The scores for all the four paws were given using the following criteria: 0, normal joints; 1, swelling in one digit or joint or minimal diffuse erythema; 2, swelling in two digits or joints or mild diffuse erythema; 3, swelling in three digits or joints or moderate diffuse erythema; 4, swelling in four digits or joints or marked diffuse erythema; 5, severe diffuse erythema and severe swelling of the entire paw and rigid joints.…”
Section: Collagen-induced Arthritismentioning
confidence: 99%
“…Elevated levels of its ligand M-CSF are observed in the joints of RA patients, contributing to the development of macrophages and osteoclasts, which are the mediators of bone erosion (21)(22)(23)(24). Blockade of the M-CSF-c-Fms axis has been shown to inhibit the progression of arthritis in animal models indicating that it may play a pivotal role in the pathogenesis of RA (25,26).…”
mentioning
confidence: 99%
“…17 In the cell contact wells, BMCs (1310 6 /well) and different numbers of activated Treg cells (2310 4 -2310 5 cells/well) were cocultured in 24-well plates for either 7 or 10 days in the presence of M-CSF (50 ng/ml) and RANKL (50 ng/ ml). In the no-contact transwell cocultures, the osteoclast precursors were loaded into the lower chambers and Treg cells were loaded into the upper chambers.…”
Section: Modulation Of Treg Cells On Osteoclast Functionsmentioning
confidence: 99%
“…3 OCs are multinucleated cells that are derived from hematopoietic precursors of the monocyte/macrophage lineage in the presence of macrophage colony-stimulating factor (M-CSF) and RANKL. [4][5][6][7] Many other cytokines have been shown to affect bone metabolism and OC activity, including interleukin (IL)-1, IL-4, IL-7, IL-10, IL-13 and TNF. [8][9][10] A previous study by our lab showed that both transforming growth factor-beta 1 (TGF-b1) and IL-10 suppress osteoclastogenesis and bone resorption in a dosage-dependent manner and exhibit synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…3 The precursors of Ocs are the monocyte/macrophage lineage of hematopoietic cells, of which proliferation and survival are dependent on macrophage colony-stimulating factor (M-CSF). 4 Thus, bone marrow-derived monocytes/ macrophages (BMMs) generate functional Ocs, when cultured in the presence of RANKL and M-CSF in vitro. The macrophage cell line RAW264 or RAW264.7, when cultured with RANKL, can also differentiate to the Oc with boneresorbing capability.…”
Section: Introductionmentioning
confidence: 99%